2020
DOI: 10.1126/sciadv.aay4900
|View full text |Cite
|
Sign up to set email alerts
|

Bright magnetic dipole radiation from two-dimensional lead-halide perovskites

Abstract: Light-matter interactions in semiconductor systems are uniformly treated within the electric dipole (ED) approximation, as multipolar interactions are considered "forbidden". Here, we demonstrate that this approximation inadequately describes light emission in novel two-dimensional hybrid organic-inorganic perovskite materials (2D HOIPs) -a class of solution processable layered semiconductor with promising optoelectronic properties. Consequently, photoluminescence (PL) spectra become strongly dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 112 publications
6
49
1
Order By: Relevance
“…Simultaneously, the two shoulders observed in the room temperature luminescence move closer together, as observed above for PDMAPbI 4 and similarly reported for Ruddlesden-Popper compounds. [25] Following similar observations for RP structures based on PEA + , the temperature-dependent spectral shifts of PDMASnI 4 are more pronounced than for the Pb-based compound: [16] For example, the energy of the higher PL peak decreases from 2.01 to 1.93 eV over the temperature range (approx. 80 vs. 30 meV; Sn vs. Pb).…”
Section: Resultssupporting
confidence: 60%
“…Simultaneously, the two shoulders observed in the room temperature luminescence move closer together, as observed above for PDMAPbI 4 and similarly reported for Ruddlesden-Popper compounds. [25] Following similar observations for RP structures based on PEA + , the temperature-dependent spectral shifts of PDMASnI 4 are more pronounced than for the Pb-based compound: [16] For example, the energy of the higher PL peak decreases from 2.01 to 1.93 eV over the temperature range (approx. 80 vs. 30 meV; Sn vs. Pb).…”
Section: Resultssupporting
confidence: 60%
“…The limited thickness of the well of C12n2 (1.2 nm thick) confines the majority of the excitonic wavefunction within two lead halide octhaedra layers, but still a small amount of OP oscillating dipoles is visible. This observation is in good agreement with previous experimental evidences, [35,36] which have shown that a small fraction of OP dipole is presents even for the n = 1 case. When n increases to four layers (2.4 nm thick), we observe a significant enhancement of the OP fraction, revealing that the OP excitonic component oscillating in the normal direction with respect to the plane of the perovskite crystal becomes more prominent.…”
Section: Optical Characterization Of 2d-pvks Single-crystalline Flakessupporting
confidence: 93%
“…[86] The birefringence of 2D perovskite crystals allows for the modulation of photoluminescence polarizations, [47] while the spatial asymmetry enables the emergence of intra-layer (bandgap) and inter-layer (in-gap) optical transitions, as shown in Figure 6b. [39,87] We found that the band-gap and in-gap states in (PEA) 2 PbI 4 polycrystalline films could be clearly resolved in the linearly polarized photoluminescence spectra collected from side view, as shown in Figure 6c,d. [38] More importantly, the two photoluminescence bands (PL-1 and PL-2) corresponding to band-gap and in-gap states show distinct polarization-dependent profiles (Figure 6e), which originates from the alignment of transition dipoles in the highly oriented (PEA) 2 PbI 4 films.…”
Section: Linearly Polarized Emission From 2d Perovskitesmentioning
confidence: 77%
“…For instance, introducing the ligands with long alkyl chains (e.g., phenethylamine (PEA)) can transform 3D perovskite into 2D structure, which turns into a natural quantum well with extremely high structural anisotropy (between in-plane and out-of-plane directions) and preferential growth orientation with respect to the substrate. [38][39][40][41][42] In comparison, organic chiral ligands (e.g., R-/S-methylbenzylammonium) can transfer their structural chirality to organic-inorganic frameworks of lead halide perovskites, and consequently introduce the separation of the circularly polarized components in bright exciton state. [43][44][45][46] The chemical modification on lead halide perovskites provides opportunities in achieving polarizationdependent optical properties based on the break of structural symmetry, such as birefringence, circular dichroism, and polarized photoluminescence.…”
Section: Introductionmentioning
confidence: 99%